Kajian Sintaksis Pragmatik terhadap Pola Kalimat Ismiyah dalam Al-Qur’an - A. Tjalau, Cutri; Sarif, Suharia; Safii, Randi (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study aims to investigate the interrelation between syntax, semantics, and pragmatics within the structure of nominal sentences (jumlah ismiyyah). Employing a syntactic-pragmatic approach, the research examines how the grammatical construction of nominal sentences influences meaning and interpretation within specific contextual frameworks. This study adopts a library research methodology, with data drawn from Qur'anic verses containing nominal sentence patterns found in Surah al-Ma'arij. Through comprehensive analysis, the study reveals that Surah al-Ma'arij features a variety of nominal sentence structures, each associated with distinct pragmatic functions. These include the expression of specification (taḫṣīṣ), continuity and permanence (al-istimrār wa al-dawām), emphasis and caution (al-ihtimām wa al-ʿināyah), as well as the acceleration of joy or adversity (litaʿjīl al-masarrat aw al-masāʾah). The findings demonstrate that nominal sentences in the Qur'anic context do not merely convey static information but also embody pragmatic dimensions that enhance the communicative impact of the text. Accordingly, this study underscores the significance of syntactic-pragmatic analysis in elucidating the intricate relationship between linguistic form and communicative function, particularly in the interpretation of religious texts such as the Qur'an